Factors affecting the corporate social responsibility disclosure (Case study at PT. Semen Tonasa). (February 2019) - Razak, L A; Ismail; Ishak; Yamin, M; Syah, A
Abstract: This study aims to determine how the influence of Corporate Social Responsibility (CSR) on Financial Performance at PT. Semen Tonasa. The type of research used in this research is quantitative descriptive. The data analysis technique used in the study was descriptive statistical analysis and multiple regression analysis. Based on the results of data analysis that has been done, it can be concluded that Corporate Social Responsibility does not affect the financial performance proxied in Return On Assets (ROA), this is because the size of the company's ROA will not change the disclosure of social responsibility by the company. Companies that have large assets do not necessarily pay attention to or show good performance through their concern for the social environment. Corporate Social Responsibility affects the financial performance proxied by Return On Equity (ROE), this means that the higher the CSR disclosure, the more ROE will increase, this shows that broad declarations provide a positive signal to interested parties, and Corporate Social Responsibility does not affect the financial performance proxied in Earning Per Share (EPS), this is because the size of the company's EPS will not affect the disclosure of social responsibility by the company, it is possible because the number of shares circulating in the company is less than optimal.